Heterosexuality in question - Jackson, Stevi; Sage eBooks (London : SAGE, 1999)
Drawing on feminism on one hand, and phenomenological and interactionist sociology on the other, this book offers an overview of recent feminist and sociological debates on heterosexuality and the construction of desire.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Women -- Sexual behavior; Heterosexuality; Feminist theory; Electronic books